John F. Griffith, 1918. - Farrell's Studio (Forsyth County Public Library, 1918)
Source: Booklet, "Winston-Salem, City of Industry," 1918.
John F. Griffith, 1918. Mr. Griffith was secretary, treasurer, and manager of the Farmers' Trade House Company.
Keywords: Digital Forsyth; Forsyth County (N.C.) -- History -- Sources; Forsyth County (N.C.) -- History -- Pictorial works